Site-selective covalent functionalization at interior carbon atoms and on the rim of circumtrindene, a C36H12 open geodesic polyarene - Cho, Hee Yeon; Ansems, Ronald B. M.; Scott, Lawrence T. (Beilstein Journal of Organic Chemistry, 2014)
Circumtrindene (6, C36H12), one of the largest open geodesic polyarenes ever reported, exhibits fullerene-like reactivity at its interior carbon atoms, whereas its edge carbons react like those of planar polycyclic aromatic hydrocarbons (PAHs). The Bingel–Hirsch and Prato reactions – two traditional methods for fullerene functionalization – afford derivatives of circumtrindene with one of the interior 6:6 C=C bonds modified. On the other hand, functionalization on the rim of circumtrindene can be achieved by normal electrophilic aromatic substitution, the most common reaction of planar PAHs. This peripheral functionalization has been used to extend the π-system of the polyarene by subsequent coupling reactions and to probe the magnetic environment of the concave/convex space around the hydrocarbon bowl. For both classes of functionalization, computational results are reported to complement the experimental observations.
Keywords: Bingel–Hirsch reaction; buckybowl; carbon nanomaterials; cyclopropanation; polycyclic aromatic hydrocarbon; Prato reaction